1993
DOI: 10.1007/bf01306079
|View full text |Cite
|
Sign up to set email alerts
|

Refractive scattering and reactions, comparison of two systems:16O+16O and20Ne+12C

Abstract: Abstract. Elastic, inelastic scattering as well as one-neutron transfer channels have been measured over a wide angular range for systems 160+ 160 at the incident energy of 350 MeV and 2~at 390 MeV, respectively, using the Q3D magnetic spectrometer. In both cases differential cross sections have been measured down to about 50 nb/sr (or da/daR <_ 10 -4) at large angles. For the 160 + 160 system refractive contributions are found at the level of these cross sections, whereas in the ZONe + l zc case a steeper dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 32 publications
3
51
0
Order By: Relevance
“…Lower: cross sections calculated with the real part of the FMP and the phenomenological imaginary potential. The experimental data are from Refs [38,39]…”
mentioning
confidence: 99%
“…Lower: cross sections calculated with the real part of the FMP and the phenomenological imaginary potential. The experimental data are from Refs [38,39]…”
mentioning
confidence: 99%
“…[14,15] at E lab = 350 MeV in comparison with OM description using the real folded potential and WS imaginary potential [24], and different cutoffs for the lowest partial wave L min ; the corresponding impact parameters are R min . The observed minimum at Θ ≈ 44…”
Section: O+mentioning
confidence: 99%
“…In the calculations the strength parameter of the imaginary potential (W V ) was fitted to reproduce the magnitude of the experimental cross sections while the radius parameter and the diffuseness parameter were fixed at around R V = 5 fm and a V = 0.3-0.5 fm, respectively. These approaches using the folding potential have been shown successful for the α and 3 He scattering from 12 C [16,17,19] over a wide rage of incident energies. The properties of the real folding potential and potential parameters used in the analysis are given in Table I.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…On the other hand, from the viewpoint of a nuclear structure study it has recently been shown that inelastic nuclear rainbow scattering is powerful in understanding the α-cluster structure of the excited states of the nucleus. For example, the α particle condensate states in 12 C and 16 O have been revealed by studying the rainbow and prerainbow in α particle and 3 He scattering from 12 C [16][17][18][19]. However, a unified study of inelastic rainbow scattering and α-cluster structure has never been undertaken for the typical α + 16 O system.…”
Section: Introductionmentioning
confidence: 99%